Demographic and Radiographic Factors Associated With Intra-articular Hip Cartilage Injury: A Cross-sectional Study of 1511 Hip Arthroscopy Procedures. Issue 11 (September 2019) - Ishøi, Lasse; Thorborg, Kristian; Kraemer, Otto; Lund, Bent; Mygind-Klavsen, Bjarne; Hölmich, Per
Background: Moderate to severe (grade 3-4) hip joint cartilage injury seems to impair function in patients with femoroacetabular impingement syndrome. Purpose: To investigate whether demographic and radiographic factors were associated with moderate to severe hip joint cartilage injury. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Patients were identified in the Danish Hip Arthroscopy Registry. The outcome variables were acetabular cartilage injury (modified Beck grade 0-2 vs 3-4) and femoral head cartilage injury (International Cartilage Repair Society grade 0-2 vs 3-4). Logistic regressions assessed the association with the following: age (<30 vs 30-50 years); sex; sport activity level (Hip Sports Activity Scale); alpha angle (AA) assessed as normal (AA <55°), cam (55°≤ AA <78°), or severe cam (AA ≥78°); lateral center-edge angle (LCEA) assessed as normal (25°≤ LCEA ≤ 39°), pincer (LCEA >39°), or borderline dysplasia (LCEA <25°); joint space width (JSW) assessed as normal (JSW >4.0 mm), mild reduction (3.1 mm ≤ JSW ≤ 4.0 mm), or severe reduction (2.1 mm ≤ JSW ≤ 3.0 mm). Results: A total of 1511 patients were included (mean ± SD age: 34.9 ± 9.8 years). Male sex (odds ratio [OR], 4.42), higher age (OR, 1.70), increased AA (cam: OR, 2.23; severe cam: OR, 4.82), and reduced JSW (mild: OR, 2.04; severe: OR, 3.19) were associated ( P < .05) with Beck grade 3-4. Higher age (OR, 1.92), increased Hip Sports Activity Scale (OR, 1.13), borderline dysplasia (OR, 3.08), and reduced JSW (mild: OR, 2.63; severe: OR, 3.04) were associated ( P < .05) with International Cartilage Repair Society grade 3-4. Conclusion: Several demographic and radiographic factors were associated with moderate to severe hip joint cartilage injury. Most notably, increased cam severity and borderline dysplasia substantially increased the risk of grade 3-4 acetabular and femoral head cartilage injury, respectively, indicating that specific deformity may drive specific cartilage injury patterns in the hip joint.